Modification of Enamel Surface Morphology and Strength Using Nd:YAG Laser with Proper and Safe Parameters - Alkaisi, Amera; Abdo, Salma B.A. (European Journal of General Dentistry, 2021)
Objective The aim of this study was to determine the effect of a Nd:YAG laser on enamel surface morphology and hardness using different energies and pulses.Materials and Methods Twenty freshly extracted mature teeth were collected and sectioned. An Nd:YAG laser operating at 1,064 nm wavelength and providing up to 9 nanosecond laser pulses (1 J), with a laser spot diameter of 0.8 mm and irradiated surface area of 3 × 3 mm2, was applied to carbon black-coated teeth. The samples were randomly divided into two main groups; each group comprised 20 samples, according to the treatment parameters. The first group was further divided into subgroups A, B1, C1, and D1 using the different energies of 0, 350, 450, and 550 mJ, respectively, with 1 pulse for B1, C1, and D1. The second group was subdivided into A, B2, C2, and D2 and treated with 200 mJ, 3, 4, and 6 pulses for subgroups B2, C2 and D2, respectively. Subgroup A was the same sample for both groups as control with 0 pulses and 0 energy. Morphological features and microhardness were evaluated after laser exposure.Statistical Analysis Analysis of variance (Kruskal–Wallis test) was used to compare all subgroups, followed by the Scheefy significant difference post hoc test to determine the highest significance of the subgroups. Alpha < 0.05 was set as significant.Results The changes in the surface morphology of the enamel included increased crystal sizes, cracks, fissures, and voids with increasing energies and pulses. In group 1, the microhardness was 405.6, 562.7, 612, and 637 for energies of 0, 350, 450, and 550 mJ, respectively. In group 2, the microhardness was 405.6, 673, 866, and 1,050 for 0, 3, 4, and 6 pulses, respectively.Conclusion The Nd:YAG laser is efficient for increasing the microhardness of the enamel surface with minimum morphological damage by applying low energy with more pulses.
Keywords: enamel; morphology; pulses; energy; Nd:YAG